AFFECTIVE DISORDERS IN PATIENTS WITH DIASTOLIC CHRONIC HEART FAILURE - V. A. Lusov; S. N. Molchanov; D. B. Gaeva; A. M. Lukashev (Российский кардиологический журнал, 2010)
The study assessed the effects of psychotropic therapy on quality of life (QoL) among patients with diastolic chronic heart failure (CHF) and concomitant affective disorders. In total, 76 patients (70 women, 6 men) were examined; in 48, anxiety and depressive disorders were observed. All participants underwent the assessment of QoL, physical functioning and affective disorder severity at baseline and 3 months after the start of the therapy. The antidepressant therapy was associated with improved physical and psychological status, as well as with improved health-related QoL.